Certification by John Travers - Travers, John, active 1804.
Certification by Travers for pork and beef, the property of Jeremiah Williams & Co.
Customs inspector, port of Georgetown, Washington, D.C.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Jeremiah Williams & Co; Beef industry; Customs administration -- Washington (D.C.); Pork industry and trade; Georgetown (Washington, D.C.); Customs inspectors